2008
DOI: 10.1007/s10549-008-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

High miR-21 expression in breast cancer associated with poor disease-free survival in early stage disease and high TGF-β1

Abstract: is considered an oncomicroRNA given its abilities to suppress the actions of several tumor suppressor genes and to promote tumor cell growth, invasion and metastasis. Recently, transforming growth factor-beta (TGF-b) is found to up-regulate the expression of miR-21, and elevated miR-21 expression is seen frequently in breast cancer. To evaluate the effect of miR-21 on disease progression and its association with TGF-b, we analyzed miR-21 expression in breast cancer. Fresh tumor samples were collected during su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
164
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(186 citation statements)
references
References 39 publications
18
164
2
2
Order By: Relevance
“…Increased TGF-b1 expression and EGFR amplification accompany the emergence of highly aggressive human carcinomas. The literature contains data supporting the fact that the polymorphisms of this gene could be associated with susceptibility to the disease, but contrasting data in the literature suggest that such polymorphisms could be protective (Noori-Daloii et al, 2007;Castillego et al, 2009;Hawinkels et al, 2009;Qian et al, 2009). No associations were detected between TGF-b1 genotype/allele frequencies and CML in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…Increased TGF-b1 expression and EGFR amplification accompany the emergence of highly aggressive human carcinomas. The literature contains data supporting the fact that the polymorphisms of this gene could be associated with susceptibility to the disease, but contrasting data in the literature suggest that such polymorphisms could be protective (Noori-Daloii et al, 2007;Castillego et al, 2009;Hawinkels et al, 2009;Qian et al, 2009). No associations were detected between TGF-b1 genotype/allele frequencies and CML in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…This study also reported a negative correlation with PTEN expression (p=0.013), a known downstream target of miR-21, in the same tissues [58]. The second study showed that high miR-21 expression was associated with features of aggressive disease, including high tumor grade, negative hormone receptor status, and ductal carcinoma, as well as a positive correlation with TGF-beta1 [59]. Although no association was found between patient survival and miR-21 expression among all patients, high miR-21 was associated with poor disease-free survival in early stage patients (HR = 2.08, 95% CI: 1.08-4.00) despite no value for prognosis.…”
Section: Clinical Significancementioning
confidence: 53%
“…Metastasis is generally associated with poor prognosis and, in some cancers, increased miR-21 expression (6,25,26). Therefore, identifying the role of miR-21 in invasion and migration can have direct clinical implications.…”
Section: Discussionmentioning
confidence: 99%